The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1108/qmr-11-2017-0153
|View full text |Cite
|
Sign up to set email alerts
|

Service failure and recovery strategies in the Balkans: an exploratory study

Abstract: Purpose Despite scholarly effort to understand customers’ recovery evaluation, little progress is evident in deciphering how customers develop online failure/recovery perception. This paper aims to address this issue. Design/methodology/approach Social constructivism was the epistemic choice for this study. This approach is holistic and offers a comprehensive understanding of each side of the phenomena. This provided social scientific descriptions of people and their cultural bases and built on, and articula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…Service failure occurs when customers' expectations are not met, whereas recovery strategies are actions that providers deliver to overcome the event (Azemi et al, 2019). Extant literature identifies two key characteristics of SFR strategies:…”
Section: Determinants and Dynamics Of Service Failurementioning
confidence: 99%
See 3 more Smart Citations
“…Service failure occurs when customers' expectations are not met, whereas recovery strategies are actions that providers deliver to overcome the event (Azemi et al, 2019). Extant literature identifies two key characteristics of SFR strategies:…”
Section: Determinants and Dynamics Of Service Failurementioning
confidence: 99%
“…(2) the most minor failures can have the highest severity if not resolved appropriately (Azemi et al, 2019;Barwise and Meehan, 2010).…”
Section: Determinants and Dynamics Of Service Failurementioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Hess et al (2003) explained the internal locus of attribution in-service failure, as customers blame themselves for service failure occurrence. Internal locus of attribution is quite untouched in preceding studies, as most of the earlier studies have correlated the causes of failure with the service-providing organizations or other external factors (Hoffman et al, 2016;Azemi et al, 2019). Although it was revealed that the nature of service failure plays a vital role in deciding whether the cause of failure is internal or external (Harris et al, 2006), only a few studies have portrayed the internal locus of attribution as a service failure factor, which lies inside the person (Heider, 1958;Vakeel et al, 2018).…”
Section: Attribution Theory and Attributions Of Service Failurementioning
confidence: 99%